Parameters Optimization and Repeatability Study on Low-Weldable Nickel-Based Superalloy René 80 Processed via Laser Powder–Bed Fusion (L-PBF) - Pietro Antonio Martelli; Antonio Sivo; Flaviana Calignano; Emilio Bassini; Sara Biamino; Daniele Ugues (Metals, 2023)
This work aims to investigate the processability of René 80 via laser powder–bed fusion (L-PBF). René 80 is a poorly weldable Ni-superalloy, currently processed via investment casting to fabricate turbine blades working at an operating temperature of about 850 °C. The L-PBF parameters optimization aims to increase part integrity and enhance processing repeatability. This part was tackled by creating a complete design of experiments (DOE) in which laser power, scan speed and hatching distance were varied accordingly. Optimizing the abovementioned parameters minimized the crack density and pore area fraction. Hence, five parameter sets leading to a crack density lower than 100 µm/mm2 and a pore fraction between 0.045% and 0.085% were selected. Furthermore, the intra-print repeatability was studied by producing three specimens’ repetitions for each optimal set of parameters in the same build. The porosity value obtained was constant among repetitions, and the crack density (around 75 µm/mm2) had a slight standard deviation. The third step of the research assessed the inter-prints repeatability by producing a replica of the five selected parameter sets in a different build and by comparing the results with those studied previously. According to this latter study, the porosity fraction (ca. 0.06%) was constant in intra- and inter-print conditions. Conversely, crack density was lower than 100 µm/mm2 only in three sets of parameters, regardless of the intra- or inter-build cross-check. Finally, the best parameter set was chosen, emphasizing the average flaw fraction (least possible value) and repeatability. Once the optimal densification of the samples was achieved, the alloy’s microstructural features were also investigated.